Earth Pressure on Retaining Wall with Surface-Inclined Cohesive Fill Based on Principal Stress Rotation. (3rd November 2021) - Wang, Hengli; Zou, Zhengsheng; Liu, Jian; Wang, Xinyu
Abstract : When considering the friction and bonding force between the back of the retaining wall and the horizontal fill behind the wall, the principal stress of the soil element near the vertical back of the retaining wall is no longer vertical and horizontal but deflects to a certain extent. When the surface of the backfill becomes inclined, the principal stress of the soil behind the wall deflects in a more complicated way. In this paper, the cohesion of the soil element in the fill with an inclined surface is assumed, and the formulas for calculating the active and passive earth pressures of the retaining wall with inclined cohesive backfill are derived by rotating the principal stress of the soil element behind the wall. The proposed method is compared with the existing algorithm, and the influences of the inclination and the cohesion of the fill are analyzed. The results show that the proposed method is more universal. Both the active and passive earth pressures increase rapidly with the increase of the inclination of the fill. The active earth pressure and its horizontal component decrease with the increase of the cohesion of the fill, while the passive earth pressure and its horizontal component increase with the increase of the cohesion of the fill.